ENHANCING THE COMPETITIVENESS OF INDONESIA’S FINANCIAL SERVICES SECTOR IN THE DIGITAL ERA THROUGH OPEN BANKING: LESSONS LEARNED FROM THE UK’S EXPERIENCE - Paripurna P Sugarda; Muhammad Rifky Wicaksono (Bank Indonesia, 2023)
In 2021, Bank Indonesia launched the National Open API Payment Standard (SNAP) to facilitate interoperable data-access for Indonesia’s digital payments sector. This article examines the lessons learned from the UK’s experience in open payments to improve the regulatory and institutional framework of Indonesia’s open banking regime. This article employs a comparative legal analysis of the UK’s open banking regime and concludes that Indonesia’s open banking regime could be improved by expanding the delivery of the Open API standards enabling interoperable data access for the entire financial services sector through an outcomes-based approach. Such expansion could be facilitated by encouraging collaboration between banks and fintechs and by creating an Open Banking App Store to increase user adoption, enhance product visibility, and widen access to digital financial services for Micro, Small, and Medium Enterprises (MSMEs)